Erianthus arundinaceus HSP70 (EaHSP70) overexpression increases drought and salinity tolerance in sugarcane (Saccharum spp. hybrid). (March 2015) - Augustine, Sruthy Maria; Narayan, J. Ashwin; Syamaladevi, Divya P.; Appunu, C.; Chakravarthi, M.; Ravichandran, V.; Subramonian, N.
Highlights: This the first report on the overexpression of EaHSP70, driven by a constitutive promoter (Port Ubi 2.3), which modulates with abiotic stresses. Overexpression of EaHSP70 conferred enhanced tolerance to drought in sugarcane. In addition it imparting salinity tolerance in food/bioenergy crop plants in general. Abstract: Heat shock proteins (HSPs) have a major role in stress tolerance mechanisms in plants. Our studies have shown that the expression of HSP70 is enhanced under water stress in Erianthus arundinaceus. In this paper, we evaluate the effects of overexpression of EaHSP70 driven by Port Ubi 2.3 promoter in sugarcane. The transgenic events exhibit significantly higher gene expression, cell membrane thermostability, relative water content, gas exchange parameters, chlorophyll content and photosynthetic efficiency. The overexpression of EaHSP70 transgenic sugarcane led to the upregulation of stress-related genes. The transformed sugarcane plants had better chlorophyll retention and higher germination ability than control plants under salinity stress. Our results suggest that EaHSP70 plays an important role in sugarcane acclimation to drought and salinity stresses and its potential for genetic engineering of sugarcane for drought and salt tolerance.